The novel coronavirus in Palestine and risk for health care worker /case report - Neveen Shalalfa; Wael Amro; Ahmad Bitawi (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Since December 2019, in Wuhan, China, a new type of coronavirus called novel coronavirus (COVID-19) was identified. The COVID-19 has then rapidly spread to all over China and the world. It can cause many symptoms including fever, difficulty in breathing and cough [1].